2011
DOI: 10.3402/ijch.v70i3.17829
|View full text |Cite
|
Sign up to set email alerts
|

Alaska Native adolescent views on cervical cancer, the human papillomavirus (HPV), genital warts and the quadrivalent HPV vaccine

Abstract: Objectives. To understand the knowledge levels, attitudes and perceptions of Alaska Native adolescent girls about cervical cancer, HPV, genital warts and the HPV vaccine. Study design. A qualitative study. Methods. Seventy-nine in-depth interviews were conducted with adolescent females aged 11 through 18 years in 4 communities in Alaska. The convenience sample was recruited through word of mouth, posters and flyers distributed in community schools, medical clinics and stores. Results. Many of those surveyed di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…These observations corroborate previous studies that documented a high prevalence of having heard of HPV and/or the HPV vaccine, 1719 but also revealed a lack of enough knowledge base to make a fully informed decision about HPV vaccination. 20,21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations corroborate previous studies that documented a high prevalence of having heard of HPV and/or the HPV vaccine, 1719 but also revealed a lack of enough knowledge base to make a fully informed decision about HPV vaccination. 20,21 …”
Section: Discussionmentioning
confidence: 99%
“…The importance of fears of serious side effects has been reinforced in surveys of adolescents 20,28 and parents 29,30 that have documented that fear about safety of these relatively new vaccines are a major reason for HPV vaccine refusal.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that different information sources may be preferred by girls of different age [18,19]. For example, information provided by health care professionals and mass media (television, the internet) seemed to be a preferred source of information among older teenage girls (15- to 18- or 19-years-old) while younger teenagers (11- or 12- to 14-years-old) had more trust in schools, teachers and family [18,19]. Guidance about HPV and HPV vaccination could therefore be provided through the preferred sources of information for different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Participants identified at least 4 areas of mutual interest, including but not limited to (a) perinatal health systems and challenges (99,100); (b) infectious disease, particularly HPV and the new vaccine (35,36,101); (c) interpersonal violence prevention; and (d) health communication and health literacy (102). The Women's Health Working group maintains an active list of ~60 members to share resources and opportunities and sponsored a pre-congress seminar on Health Literacy and Northern Women's Health in Fairbanks in August 2012 that attracted ~50 participants.…”
Section: Outreach Education and Communicationmentioning
confidence: 99%